Cross Cultural Understanding and Islamic Academic Values (BudAI) Preservation of the Students upon Graduation from College of Language (FB) Unissula - Idha Nurhamidah . (Dinamika Bahasa dan Budaya, 2018)
This study aims to analyze the level of ‘Cross Cultural Understanding (CCU) and the Islamic Academics Values (BudAI) preservation' of prospective graduates of college of Languages (FB) Unissula term 1, April 2017, who are 52 candidates as reported, as basis of academic policy making. Survey method with the instrument of an on-line questionnaire is used to investigate the tendency of prospective graduates towards 'cultural diversity', by utilizing the ‘questionnaire form’ provided by 'google sheet'. The results of this study indicate a positive mood that graduate candidates are equipped with sufficient CCU and BudAI which enable them to work globally or cross-culturally adjusted but still affirmed themselves to Islamic values. These are the identity of Unissula graduates as part of eastern culture. This study is only at the cognitive level, and therefore, further researches are recommended with the other methods of observation and in-depth interview after certain period of time, both to the students (self-observation) and interviews with related parties (graduate users) to reveal the level of CCU and BudAI preservation of  FB Unissula graduation in the motoric and affective level. Keywords: Cross Cultural Understanding, BudAI preservation, Academic policy